Paper bullets : two artists who risked their lives to defy the Nazis - Jackson, Jeffrey H., 1971- (Algonquin Books of Chapel Hill, 2020)
"The true story of an audacious resistance campaign undertaken by an unlikely pair: two French women--Lucy Schwob and Suzanne Malherbe --who drew on their skills as Parisian avant-garde artists to write and distribute wicked insults against Hitler and calls to desert, a PSYOPs tactic known as 'paper bullets,' designed to demoralize Nazi troops occupying their adopted home of Jersey in the British Channel Islands"--